Day One : Before Hiroshima and After - Wyden, Peter (New York Simon and Schuster, 1984)
Examines the events leading to the creation and use of the atomic bomb.
Include Illustrations, Notes, Bibliography and Index.
Keywords: Japan -- World War (1939-1945) -- Atomic bomb -- Japan--Hiroshima-shi -- Bombardment of Hiroshima-shi (Japan : 1945) -- Terrorism -- England--London -- Falkland Islands War (1982)